High Refractive Index Hyperbranched Polymers Prepared by Two Naphthalene-Bearing Monomers via Thiol-Yne Reaction - Wei, Qiang; Zan, Xingjie; Qiu, Xianping; Oktem, Gozde; Sahre, Karin; Kiriy, Anton; Voit, Brigitte (Macromolecular Chemistry and Physics, 2016)
High refractive index (HRI) materials play an important role in optic-electronic devices. In this study, two compounds with high content of naphthalene groups, 1,5-dithiolnaphthalene and 1,3,5-tris(naphthalyl–ethylnyl) benzene, are selected as “A2” and “B3” monomers, respectively to prepare hyperbranched HRI polymers. Metal-free radical-initiated “A2 + B3” thiol-yne polyaddition is conducted successfully at different monomer molar ratios even for those sterically demanding molecules being able to adjust the molar mass as well as RI. Polymers with refractive index up to 1.79 at 589.7 nm are obtained, which are among the highest RI values so far reported for pure polymer-based materials. The high RI, based on the high molar refraction of naphthalene group, metal-free and easy one-pot synthesis, high transparency in the visible area, good thermal stability, good solubility, and easy processability into thin films, make these polymers excellent candidates for optic-electronic applications. (Figure presented.).
CRIS-Team Scopus Importer:2023-03-20
Keywords: high refractive index; hyperbranched polymers; naphthalene; thiol-yne